Serious game & virtual reality manual - Gomes, Lisa (2023)
Welcome to an intellectual and emotional journey! This preface introduces a manual dedicated to Serious Games and Virtual Reality, focusing on the development of emotional competence. Our journey begins with the recognition of the exceptional efforts and unwavering dedication of those who made this endeavor possible. It is a testament to the power of collaboration and commitment, thanks to esteemed partners like the Polytechnic University of Bragança, the University of León, the University of Genoa, the University of Malta, and the Ştefan cel Mare University of Suceava. The roots of this journey trace back to 2018 at the University of Minho when visionary professors from the School of Nursing identified a gap in nursing education—while technical proficiency was emphasized, emotional intelligence was often overlooked. Thus, they conceived the idea of incorporating emotional competence into the education of future health professionals, aligning it with the demands of our digital age. As this vision gained momentum, it became evident that the challenge extended beyond their institution. Teaching emotions to students was indeed a complex task, prompting them to seek innovative approaches to nurture these essential skills.